2023
DOI: 10.1128/mbio.03386-22
|View full text |Cite
|
Sign up to set email alerts
|

cotH Genes Are Necessary for Normal Spore Formation and Virulence in Mucor lusitanicus

Abstract: Current treatment options for mucormycosis are inadequate, resulting in high mortality rates, especially among immunosuppressed patients. The development of novel therapies for mucormycosis has been hampered by lack of understanding of the pathogenetic mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…The disruption of five of them led to defects in temperature adaptation and cell wall development. More importantly, their role in virulence was confirmed in a mouse model [ 20 ] ( Table 1 ). Besides some bacteria and Mucorales , CotH proteins are not found in other fungi such as Candida and Aspergillus, making them a specific target for therapeutic and diagnostic approaches [ 21 , 57 ].…”
Section: Genes Involved In the Pathogenic Potential Of Muco...mentioning
confidence: 97%
“…The disruption of five of them led to defects in temperature adaptation and cell wall development. More importantly, their role in virulence was confirmed in a mouse model [ 20 ] ( Table 1 ). Besides some bacteria and Mucorales , CotH proteins are not found in other fungi such as Candida and Aspergillus, making them a specific target for therapeutic and diagnostic approaches [ 21 , 57 ].…”
Section: Genes Involved In the Pathogenic Potential Of Muco...mentioning
confidence: 97%
“…The CotH family of kinases, originally found in Bacillus subtilis (involved in the production of endospores), serves as receptors for human GRP78 during mucormycosis. Szebenyi et al identified 17 homologous genes of CotH in the Mucor lusitanicus genome, and disruption of various CotH genes revealing their significant roles in pathogenesis as listed in Table …”
Section: Virulence Factors Involved In Pathogenesismentioning
confidence: 99%
“…Szebenyi et al identified 17 homologous genes of CotH in the Mucor lusitanicus genome, and disruption of various CotH genes revealing their significant roles in pathogenesis as listed in Table 2. 98 The pathogenicity of mucormycosis etiological agents relies on the number of CotH genes as observed in the genome of Rhizopus, Mucor, and Lichtheimia genera, which are associated with invasive infections. 88,100,101 Structural analysis revealed analogous interactions between GRP78 and CotH3 and CotH2 via modeling and docking.…”
Section: Pathogenesismentioning
confidence: 99%
“…They facilitate quantification of messenger RNA (mRNA) or transfer RNA (tRNA) through quantitative PCR, reverse transcriptase PCR and modified-induced misincorporation tRNA sequencing (mim-tRNASeq) ( 78 , 79 ). The gene editing tool CRISPR/Cas9 utilises guide RNA which matches with target gene (CRISPR) and CRISPR-associated protein 9 (Cas9), an endonuclease which helps to break the dsDNA and facilitate editing of the target gene ( 80 ) and it can be used for loss-of-function studies ( 12 , 45 , 81 ). Bioinformatics tools have been developed and adapted for genomic studies across microbial, Drosophila and human genomes and these allow for rapid screening of genomes and vast publicly available pathogen and fly data for potential targets for further study ( 79 , 82 ).…”
Section: Application Of Drosophila To Human Fungal...mentioning
confidence: 99%